Activated carbon monoliths with hierarchical pore structure from tar pitch and coal powder for the adsorption of CO2, CH4 and N2. (July 2016) - Arami-Niya, Arash; Rufford, Thomas E.; Zhu, Zhonghua
Abstract: Activated carbon monoliths with hierarchical pore structures were prepared from petroleum tar pitch and powdered coal in a low pressure foaming process with potassium hydroxide activation. The effects of coal to tar pitch ratio and of the amount of potassium hydroxide on the stability of tar pitch during the foaming process, the product's density and the micropore structure were studied. The carbon monolith prepared with adding 50%wt coal to pitch retained the shape of the cylindrical foam mould. This carbon monolith featured an open-cell structure with cell widths of around 2 μm and a well-developed microporosity that presented a BET specific surface area of 1044 m 2 g −1 . The apparent density of this structure was 0.42 g cm −3 . The adsorption capacity of the carbon monolith for CO2, N2 and CH4 were evaluated by the volumetric sorption method at pressures up to 130 kPa and by a gravimetric sorption method for pressures up to 4500 kPa. At 298 K and pressures close to 3500 kPa the adsorption capacities of the carbon monolith prepared with 50%wt coal to pitch were 7.398 mol kg −1 CO2, 5.049 mol kg −1 CH4 and 3.516 mol kg −1 N2 . The sorption results suggest these activated carbon monoliths have potential as monolithic adsorbents for gas separation or storage applications.